1965
DOI: 10.1121/1.1909837
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Identify Complex Sounds: Prompting versus Confirmation

Abstract: Three groups of subjects were taught to identify, by label, complex sounds. With temporal overlap controlled, confirmation and prompting training procedures were compared. Despite recent emphasis on the superiority of prompting procedures, no significant difference in the efficacy of the two methods was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is considerable research indicating that performance on perceptual tasks is susceptible to improvement with training (e.g. Ahissar, 1999Ahissar, , 2001Aiken & Lau, 1967;Annett, 1966;Annett & Patterson, 1967;Cuddy, 1968;Lunn, 1948;Prather, Berry, & Bermudez, 1972;Proctor & Dutta, 1995;Sidley, Winograd, & Bedarf, 1965;Swets, Millman, Fletcher, & Green, 1962), including perceptual learning specific to audition (Cuddy, 1968). Cuddy's results indicated not only that training could alter the performance of untrained subjects, but also that the focus of the training programme was an important factor in the amount of improvement attained (Cuddy, 1968;Heller & Auerbach, 1972).…”
Section: Context and Training In Sonification Tasksmentioning
confidence: 99%
“…There is considerable research indicating that performance on perceptual tasks is susceptible to improvement with training (e.g. Ahissar, 1999Ahissar, , 2001Aiken & Lau, 1967;Annett, 1966;Annett & Patterson, 1967;Cuddy, 1968;Lunn, 1948;Prather, Berry, & Bermudez, 1972;Proctor & Dutta, 1995;Sidley, Winograd, & Bedarf, 1965;Swets, Millman, Fletcher, & Green, 1962), including perceptual learning specific to audition (Cuddy, 1968). Cuddy's results indicated not only that training could alter the performance of untrained subjects, but also that the focus of the training programme was an important factor in the amount of improvement attained (Cuddy, 1968;Heller & Auerbach, 1972).…”
Section: Context and Training In Sonification Tasksmentioning
confidence: 99%
“…The successful implementation of auditory graphs requires perceptual skill, and research has indicated that perceptual performance can be improved with training (Ahissar, 2001;Aiken & Lau, 1967;Annett, 1966;Annett & Patterson, 1967;Prather, Berry, & Bermudez, 1972;Sidley, Winograd, & Bedarf, 1965;Swets, Millman, Fletcher, & Green, 1962). In many traditional perceptual training paradigms, prompting of correct responses or feedback for correct responses have been employed to improve perceptual acuity.…”
Section: Introductionmentioning
confidence: 99%